Un análisis lógico-semántico del recuerdo - Forero-Mora, José Andrés; Álvarez-Ariza, Jesica Sabina (Disputatio, 2020)
There are different philosophical positions about remembering that have studied, among other things, what its epistemic role or its psychological functioning is. However, not much have been said about this matter from philosophy of language. For this reason, we present a logical-semantic analysis that allows us to state that the act of remembering has an expressive function rather than a merely descriptive one. The actions that speakers perform when they talk about their memories go beyond of giving some information that refers to facts and contents about past personal experiences. We explore the pragmatic dimension of that act based on three kinds of memory. Firstly, factual memories with which speakers acquire epistemic and assertional commitments. Secondly, personal memories with which speakers also acquire those commitments but, in addition, evaluate their past from the present and invite others to share that evaluative position. Thirdly, perceptual memories with which speakers also can acquire those commitments, but what they mainly do is to move a content from the past to the present. The analysis shows 1) some essential aspects of the phenomenon of remembering and 2) that its complexity is much greater than that which some epistemic or psychological researches usually recognize